Various Clinical Overviews in Pelvic Cavity Cancer In “Dharmais” National Cancer Hospital (DNCH) - Evlina Suzanna; Asri C Adisasmita; Pradnya Sri Rahayu; Grace Shalmont (http://dharmais.co.id/, 2023)
Background: Pelvic cavity is formed by the bones of pelvic organs where there are many system organs. Pelvic cavity cancer incidence in Jakarta from 2005 to 2007 was 13.96/100.000 population. In “Dharmais” National Cancer Hospital (DNCH), the frequency in 1993-2007 was 26% of all cancer. The purpose of the research is to find an overview of epidemiological (age group, gender, domicile, educational, marital status, tumor location) and clinical (symptoms and stage) cancer pelvic cavity. Methods: This cross-sectional study used the medical records of patients registered with DNCH as new cases and diagnosed by microscopic examination during 2005-2007. The study population is a case of cancer with the diagnosis of the location of the primary tumor in the pelvic cavity area. The sample calculation used a precision formula and obtained a minimum sample of 323. The data collection used questionnaires and obtained 326 cases. The data were analyzed using SPSS 26.0 with Chi-square test (α = 0.05).Results: Pelvic cavity cancer is a major problem in females (91.1%) with peak ages 45-59. Variations of clinical features in males and females were 24 and 35 symptomatic. In males, the most common clinical feature is dark/blood stool (41.38%), generally on rectal cancer, followed by weight loss (20.69%) which overlaps at five organs. In females, the most common clinical features are vaginal bleeding (43.77%), and vaginal spotting (13.47%), which occurs in cervix cancer, followed by abdominal pain (13.47%) that overlaps in six organs. Conclusions: Cancer, especially primary tumors of the pelvic cavity, is not a “silent killer” disease because the clinical picture can appear at an early stage. This study also provides a common clinical picture in patients with primary tumors in the pelvic cavity even though they are in one cavity. The clinical picture that appears is specific according to the primary tumor. In addition, some symptoms are possessed by various organs, so they are nonspecific.